D-Day in History and Memory : The Normandy Landings in International Remembrance and Commemoration - Dolski, Michael, 1978-; Edwards, Sam, 1981-; Dolski, Michael, 1978- (Book collections on Project MUSE., 2014)
Over the past seventy years, the Allied invasion of Northwestern France in June 1944, known as D-Day, has come to stand as something more than a major battle. This book examines the commonalities and differences in national collective memories of D-Day.